First Results of Robot Assisted Radical Prostatectomy in Klaipėda University Hospital: Single Center Experience - Venckus, Raimundas; Jasėnas, Marius (Lietuvos chirurgija, 2019)
[full article and abstract in Lithuanian; abstract in English]Robot-assisted radical prostatectomy (RARP) has become the main surgical option for localised prostate cancer. We analyzed RARP results in Klaipeda university hospital using Senhance® robotic system. We report our early experience with first 23 patients operated using Senhance® robotic system. Patients and methods. This is single center case series included first 23 patients undergoing RARP in Klaipeda university hospital, Lithuania during period from November 21, 2018 to March 1, 2019. All the data including surgical complications were recorded. Results. Operation time average was 3 hours and 36 minutes. 2 (8,7%) complications were recorded. After the initial 23 cases patients was completely pad free 81,8 % in early postoperative time. The limitations of the present study is small patients group, uncontrolled nature and short follow up time. Conclusion: We demonstrated that RARP with Senhance® robotic system is safe and feasible, and our results are similar compared to those achived with other robotic system.
Keywords: Robotic surgery; radical prostatectomy; Senhance robotic system